Li fast ion conductive La0.56Li0.33TiO3 inlaid LiFePO4/C microspheres with enhanced high-rate performance as cathode materials. (10th January 2015) - Shu, Hongbo; Chen, Manfang; Wen, Fang; Fu, Yanqing; Liang, Qianqian; Yang, Xiukang; Shen, Yongqiang; Liu, Li; Wang, Xianyou
Highlights: Various content of La0.56 Li0.33 TiO3 inlaid LiFePO4 /C are firstly prepared by an ammonia assisted hydrothermal route. The inlaid La0.56 Li0.33 TiO3 can enhance the transfer kinetics of both Li + and electrons. Among all of samples, 2  wt. % La0.56 Li0.33 TiO3 inlaid LiFePO4 /C shows the best rate capability and cycling stability. La0.56 Li0.33 TiO3 inlaid LiFePO4 /C is an effective way to improve the performance of LiFePO4 power battery. Abstract: Monodisperse spherical La0.56 Li0.33 TiO3 inlaid LiFePO4 /C composites with various La0.56 Li0.33 TiO3 content (from 0  wt . % to 3  wt. %) are firstly prepared by an ammonia assisted hydrothermal route. The compositions, morphology and structure of samples are characterized by means of inductively coupled plasma (ICP), X-ray diffraction (XRD), scanning electron microscope (SEM), transmission electron microscopy (TEM), energy dispersive spectrometer (EDS), respectively. The results reveal that nano La0.56 Li0.33 TiO3 particles inlay on the surface of spherical LiFePO4, which is coated by a continuous and uniform carbon layer with the thickness of 1∼2 nm. The charge/discharge tests and electrochemical impedance spectroscopy (EIS) measurements indicate that the kinetics of La0.56 Li0.33 TiO3 inlaid LiFePO4 /C is better than that of LiFePO4 /C. With the change of La0.56 Li0.33 TiO3 content, 2  wt. % La0.56 Li0.33 TiO3 inlaid LiFePO4 /C composites reveal a excellent high-rate capability and cycling stability. The initial discharge capacity of the sample is 126.3 and 108.9 mAh/g, and the capacity retention achieves as high as 98.3% and 88.8% till 100 cycles at 5 C and 200 cycles at 10 C, respectively. Furthermore, it still exhibits a high discharge capacity of 62.3 mAh/g even at high rate of 30 C. The improved electrochemical performance of La0.56 Li0.33 TiO3 inlaid LiFePO4 /C composites can be attributed to reduce the charge transfer resistance and enhance the transfer kinetics of both the lithium ions and electrons.